Surface roughness optimization and high-temperature wear performance of H13 coating fabricated by extreme high-speed laser cladding. (May 2022) - Yan, Q; Yang, K; Wang, ZD; Chen, MZ; Sun, GF; Ni, ZH
Highlights: The coatings showed a low roughness and a large thickness without defects when the overlap ratio was 70%. Formation mechanism of the adhered powders during the EHLA cladding was proposed. The response surface analysis was conducted to investigate the effect of parameters on the width of the single-track to keep the overlap ratio constant. High-temperature wear properties of the H13 coatings and the 5CrNiMo substrate were compared. Abstract: Extreme high-speed laser (EHLA) cladding, which refers to metal deposition at speeds > 20 m/min, is the optimization for conventional laser cladding. Improving the surface properties of 5CrNiMo die steel has always been a research hotspot during engineering application. However, few research reported the enhancement of 5CrNiMo properties by EHLA cladding. The present study aims to optimize the surface roughness and analyze the high-temperature wear performance of the coatings produced by EHLA cladding. Results indicated that a laser power (4000 W), a reasonable scanning speed (376.8 mm/s) and a proper powder feeding rate (20.64 g/min) were essential for achieving the coatings with a low roughness and a large thickness without defects when the overlap ratio is 70%. In addition, the formation mechanism of the adhered powders during the EHLA cladding was discussed. The increase of the velocity and radius of the powders could reduce the adhered powders. Furthermore, the response surface analysis was conducted to investigate the effect of parameters on the width of the single-track to keep the overlap ratio constant. Additionally, friction and wear tests were carried out to discuss the tribological properties of the coatings and the 5CrNiMo substrate. The oxide film on the surface of the H13 coating enhanced the tribological property.